SPECT-CT localization of axillary sentinel lymph nodes for radiotherapy of early breast cancer - Novikov, Sergey (Rep Pract Oncol Radiother, 2019)
PURPOSE: To evaluate the opportunities of single photon emission tomography/computerized tomography (SPECT-CT) for localization of axillary sentinel lymph nodes (ASLNs) and subsequent radiotherapy planning in women with early breast cancer. MATERIAL AND METHODS: Individual topography of ASLN was determined in 151 women with clinical T1-2N0M0 breast cancer. SPECT-CT visualization of ASLNs was initiated 120 min after intra-peritumoral injection of 99mTc-radiocolloids. Doses absorbed by virtual ASLNs after the whole breast irradiation with standard and extended tangential fields were calculated on a treatment planning station. RESULTS: SPECT-CT demonstrated a large variability of ASLN localization. They were detected in the central subgroup in 94 (61%) patients, in pectoral – in 77 (51%), and in interpectoral – in 4 (3%) patients. Sentinel lymph nodes “lying on the chest” were revealed in 35 (23%) cases. We found that with standard tangential fields coverage of ASLNs was obtained only in 20% of evaluated women. Extended tangential fields can effectively irradiate ASLNs localized in all axillary sub-regions with the exception of ASLNs “lying on the chest”. CONCLUSION: SPECT-CT mapping of ASLNs in women with cT1-2N0M0 breast cancer reveals their variable localization. This information can be important for planning of radiation treatment in women that underwent breast conserving surgery without an axillary surgery.